POTENTIAL HERB-DRUG INTERACTION OF DECALEPIS HAMILTONII VIA P-GP MEDIATED PHARMACOKINETIC INTERACTION WITH FEXOFENADINE IN RATS: AN IN SITU AND IN VIVO STUDY - SANDOPA, DHANUNJAYA; VELLAPANDIAN, CHITRA (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of this study was to investigate the influence of Decalepis hamiltonii (D. hamiltonii), a traditional plant used in herbal medicine, on the intestinal absorption and pharmacokinetics of fexofenadine, a substrate of P-glycoprotein (P-gp), in rats. Methods: In situ intestinal perfusion tests were conducted to assess the intestinal permeability of fexofenadine. P-gp ATPase activity was also evaluated to understand the modulatory effects of D. hamiltonii on P-gp. An in vivo pharmacokinetic investigation was performed by administering oral fexofenadine to rats. Results: The in situ study results revealed that the effective permeation (Peff) of fexofenadine was significantly diminished (p<0.001***) in aqueous extract of D. hamiltonii (AREDH, 200 mg/kg p. o.) pretreated group compared to normal control indicating modulation in absorption. Further, there was significant augmentation (p<0.01**) of P-gp ATPase activity in AREDH pretreated group (200 mg/kg p. o.) compared normal control indicating P-gp inductive potential of D. hamiltonii. Pharmacokinetic study results revealed that the peak plasma concentration (Cmax) and the area under the concentration-time curve (AUC) of fexofenadine was significantly downregulated (p<0.001***) in AREDH pretreated group (200 mg/kg p. o.) compared to the normal control group indicating the compromised absorption and bioavailability. However, no significant changes were observed in fexofenadine half-life (T1/2 k10), time to reach peak plasma concentration (Tmax), or elimination rate constant (k10). Conclusion: In conclusion, D. hamiltonii significantly reduced the oral bioavailability of fexofenadine by promoting P-gp-mediated drug efflux during intestinal absorption. This suggests that the modulatory characteristics of D. hamiltonii may lead to herb-drug interactions when taken in combination with xenobiotics, emphasizing the importance of considering such interactions in clinical practice and further research.